Diluted seawater decreased weight gain and altered blood biochemical parameters in Bach Thao goats - Thiet Nguyen; Ngu Nguyen Trong; Narongsak Chaiyabutr; Sumpun Thammacharoen (Journal of Applied Animal Research)
This study aimed to evaluate the effect of saline water (SW) on physiological responses, blood biochemical parameters and body weight changes in Bach Thao goats. The study was designed completely randomized with four treatments (n = 5 each), including a control as goats’ drinking fresh water (FW), goats’ drinking 0.5% SW (LSW, low SW), goats’ drinking 1.0% SW (MSW, moderate SW) and goats’ drinking 1.5% SW (HSW, high SW). The results showed that dry matter intake (DMI) decreased as SW increased (P < 0.05). Animals in the MSW group consumes highest water intake (WI), whereas animals from HSW consumed least water from 4th to 8th weeks of experiment. Respiration rate and rectal temperature in HSW were greater than those in the FW group (P < 0.05). The body weight was similar among treatments, but animals in HSW were with lower weight gain than those in the control (P < 0.05). Goats in HSW altered blood biochemical parameters in the 8th week, not for the 4th week. We concluded that Bach Thao goats drank high SW within 56 days and had negative effects on production and may effect on functions of the liver and kidney. Besides, goats from the HSW group have decreased daily WI to minimize the salt stress.